In Vitro Evaluation of Cytotoxicity Effect of Ihau Fruit Extract (Dimocarpus longan var. Malesianus Leenh.) on MCF-7 Breast Cancer Cell Line - Wyna Nabila; Irma Sarita Rahmawati; Ghina Putri Dyanti; Rahma Micho Widyanto; Annisa Rizky Maulidiana; Ratna Chrismiari Purwestri (Indonesian Journal of Human Nutrition, 2023)
Cancer prevalence is steadily increasing each year and becomes the second leading cause of death worldwide. In Indonesia, breast cancer had a prevalence of 16.7% in 2018. Free radicals contribute to the occurrence of breast cancer, while antioxidants play a vital role in protecting cells and repairing the damage caused by free radicals. Ihau, an endemic fruit in Kalimantan Island, contains phytochemical compounds with potential antioxidant and anticancer properties. Utilizing local food as natural antioxidants could serve as an alternative for breast cancer prevention and treatment. This study aims to assess the anticancer potential of Ihau fruit extract on the MCF-7 breast cancer cell line. A post-test-only control group design method using the MTT assay was used, with two treatment groups: water and 96% ethanol extract, and four different concentrations (125, 250, 500, and 1000 ppm), and each was replicated three times. Statistical analysis using the ANOVA test found no significant difference among all concentrations. The IC50 values of the cytotoxic activity of water and ethanol extracts were 1,197.7 ppm and 1,148 ppm, respectively. It can be concluded that both water and ethanol extract of Ihau fruit exhibited very weak cytotoxic activity.